Characterization of the sulfation reactivity of limestones with different particle size in a large-capacity TGA. (1st July 2020) - Li, Yiran; Cai, Runxia; Zhang, Man; Yang, Hairui; Lyu, Junfu
Highlights: The effects of particle size on sulfation was studied under various conditions. Fine limestones are less sensitive to the variation in SO2 concentrations. A model was established to predict the effects of particle size on sulfation. The effects of particle size mainly depend on the reaction on external surface. Abstract: Limestone particle size has a significant influence on the desulfurization effect in CFB boilers. However, few studies have focused on the effects of particle sizes under different conditions. As a result, many existing sulfation models have deficiencies in predicting the sulfation process of limestones with a broad range of particle sizes. In this paper, the sulfation process of limestone with a broad range of particle sizes was investigated under different SO2 concentrations, CO2 concentrations, and temperatures by using a large-capacity TGA. A semi-empirical model was established based on the experimental results. It is found that the fine limestone exhibited the superior desulfurization performance compared with the coarse limestone, and it is less sensitive to the variation in SO2 concentrations. The highest ultimate conversion achieved at 850 °C–900 °C, and showed little difference between different particle sizes. Besides, the conversion and initial reaction rate increase slightly with the CO2 concentrations. The established model divided the sulfation process of limestone into the direct contact reaction on the external surface and the diffusion-controlled reaction on the inner pore surface, which can well predict the particle sizes under different SO2 concentrations.